Educational research trends in ICT - Sharifah Sariah Syed Hassan; Che noraini hashim (IIUM Press, 2014)
This book was compiled based on the research work and articles writteny by the main author Dr Sharifah Sariah and her students during the courses of Issues and Research in Instructional technology and Distance Learning